Pelaksanaan Kinerja Satuan Polisi Pamong Praja Dalam Menegakkan Pelanggaran Peraturan Daerah di Kabupaten Blora (Studi Kasus Perda No. 7 Tahun 2015) - Rizal Khairul Amri; Priyatno Harsasto . (Journal of Politic and Government Studies, 2017)
ABSTRACT This essay entitled "Implementation of the Civil Service Police Unit Performance In Enforcing Violations Local Regulation in Blora". Under the auspices of Drs. Priyono S, M.Si as a mentor I and Drs. Ghulam, S.Sos.M.Si as a mentor II. In this study, the authors brought the performance issue of satuan kerja perangkat daerah (SKPD) with a research focus onSatuan Polisi Pamong Praja (Satpol PP) in Blora, as well as the subject matter defined in this study were: 1). How well the Satuan Polisi Pamong Praja carry out their duties in enforcing peace and order in Blora? 2). How well the Satuan Polisi Pamong Praja in Blora carry out their duties without discrimination? 3. How good Satuan Polisi Pamong Prajaperformance to follow up the enforcement that have been carried out in accordance enforcement of legislation in Blora?This study aims to determine; 1) To determine the Satuan Polisi Pamong Praja performance carrying out their duties in enforcing peace and order in Blora; 2). To determine the Satuan Polisi Pamong Praja performance in Blora carrying out their duties without discrimination; and 3). To determine Satuan Polisi Pamong Praja performance on following up the enforcement that have been carried out in accordance enforcement of legislation in Blora. This research was conducted in the Office of the Satuan Polisi Pamong Praja in Blora. In this study, the theory used by the authors is the theory of performance appraisal belongs to Agus Dwiyanto (2006) which consists of the following five indicators of productivity, cauldron bags of service, responsiveness, responsibility and accountability. The method used in this research is descriptive quantitative method. The researcher’s technique used in data collection were questionnaires, interviews, observation and documentation. This study uses a sampling technique with area proportional random sampling method which is mean the data collection method takes a sample proportionately and randomly in each area with a population sample of 100 respondents. The data have been analyzed by using qualitative analysis. The results of this study showed that the Satuan Polisi Pamong Praja performance carrying out their duties in enforcing peace and order in Blora poorly because only reached 63,71%. This means that the performance of the Satuan Polisi Pamong Praja does not run well. It is known that there are three indicators have no good results, namely productivity, responsibility and accountability, while there are two indicators that get good results and thereare quality of service and responsiveness. This means that according to the performance of the Satuan Polisi Pamong Praja in Blora carrying out their duties without discrimination. As for the performance of Satuan Polisi Pamong Praja to follow up the enforcement that have been carried out in accordance of legislation enforcement in Blora, there are some things that must be addressed to improve the services performance and the quality of human resources, competencies and motivation, improved infrastructure, and further enhance the quality of the relationship of coordination with investigators Indonesian National Police (INP) and related agencies, and should always work in accordance with the rules and operational guidelines applicable, should also be more likely to disseminate to the public so that people know the role and function of Satuan Polisi Pamong Praja. Key Word : Performance, Satuan Polisi Pamong Praja, Local regulation violation